An evidence-based tailored eHealth patient education tool for patients with knee osteoarthritis: A randomized controlled trial - Chong Li; Chuanmei Zhu; Kangping Song; Xiaona Xiang; Xiaoyi Wang; Jing Hu; Zhao Li; Yi Deng; Daoxin Jiang; Lixin Guo; Ting Ren; Luwen Zhu; et al. (Digital Health)
Background An evidence-based eHealth education tool was developed for patients with knee osteoarthritis (KOA). This study aimed to evaluate the long-term effectiveness on patient knowledge level and analyzed the patient's satisfaction with the proposed tool. Methods A two-arm randomized controlled trial was performed, with 218 KOA patients allocated 1:1 to two groups by balanced block randomization. Both groups received usual care and additionally, the eHealth group used the proposed eHealth tool during the process. The primary outcome measure was the validated osteoarthritis patient knowledge questionnaire (PKQ-OA). The secondary outcome was patients’ satisfaction with the eHealth tool. Measurements were taken at baseline, post-intervention (T1), 1-month (T2), 3-month (T3), and 6-month (T4) follow-up. Statistical analyses, including ANOVA and chi-square tests, were employed to compare outcomes between the groups. Results The results of the PKQ-OA indicated that patients in the eHealth group (38.7% ± 25%, 95% confidence interval (CI), 33.9%–43.4%) performed significantly better than the usual care group (28.8% ± 21.1%, 95% CI, 24.9%–32.9%) in terms of correct responses to the knowledge assessment in T1( P  = 0.001). In addition, a higher percentage of patients in the eHealth group (39.4%) achieved a score of at least 50% on the knowledge assessment compared to the usual care group (14.6%). Patients who received eHealth education perceived it as a valuable tool for education. The analysis of follow-up data showed that the knowledge level of the eHealth group was higher than that of the control group at 6 months ( F  = 0.727, P  = 0.471), but there was no significant difference. Conclusion Patients educated using an evidence-based eHealth education tool showed significant improvements in knowledge and were more likely to achieve an adequately informed status. The evidence-based eHealth tool could offer a low-cost, effective educational device.